-2(r+9)=33

Simple and best practice solution for -2(r+9)=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(r+9)=33 equation:



-2(r+9)=33
We move all terms to the left:
-2(r+9)-(33)=0
We multiply parentheses
-2r-18-33=0
We add all the numbers together, and all the variables
-2r-51=0
We move all terms containing r to the left, all other terms to the right
-2r=51
r=51/-2
r=-25+1/2

See similar equations:

| –11x−–10x=9 | | 2x+4(-x+3)-4=0 | | 11x+39=−16 | | 180=50+(y+10)+2y | | -5.6(x-2.75)=11.2 | | X2º+b2º=30 | | z-3/16=7/16 | | -(x-1)+2(3-x)=-2 | | 15c+85=c | | {11(y-10)}=(4y-5 | | 10-4×=3y | | 2/3=2x-7/3x+4 | | (x+19)=(5x-45) | | -6k=6-6k | | 180=(y+10)+2y | | 3m−2m=5 | | –10−2h=–3h | | 6(3x+1)=-102 | | 58=8+5n | | 13x+4=27x-2 | | 8-2(4x-3)=-26 | | 2(x+2)-2=4x-2(-3+x) | | 3.2=-0.4nn= | | 5(w+7)=-5(3w-4)+2w | | 3+6b=2b+3b | | −12(3x−4)=11 | | 2(x+2)-2=4x-2(-3+x | | 1233.99=172x+19.99 | | 17−3x+15=8x+30 | | X+(b)=30 | | 3900=4x+5x | | -5x-11=+64 |

Equations solver categories